International diversification gains and home bias in banking - García-Herrero, Alicia; Vázquez, Francisco (Journal of Banking & Finance, 2013)
This paper studies international diversification in banking, exploiting a bank-level dataset that covers the operations of 38 global banks and their subsidiaries overseas during 1995–2004. The paper finds that banks with a larger share of assets allocated to subsidiaries in emerging market countries were able to attain higher risk-adjusted returns. These gains were somewhat reduced by the concentration of bank subsidiaries in specific geographical regions, which is typical of the observed international expansion strategies. The paper also finds a substantial home bias in the international allocation of bank assets relative to the results of a mean–variance portfolio optimization model.